Laser CO2 tonsillotomy versus argon plasma coagulation (APC) tonsillotomy: A retrospective study with 10-year follow-up. (January 2017) - Papaspyrou, Giorgos; Linxweiler, Maximilian; Knöbber, Dirk; Schick, Bernhard; Al Kadah, Basel
Abstract: Introduction: Tonsillotomy is increasingly gaining acceptance as the treatment for tonsillar hyperplasia resulting in obstructive symptoms. The aim of this study was to compare the long-term results of CO2 laser tonsillotomy with those of argon plasma coagulation (APC) tonsillotomy. Methods: The data of 64 children, aged 2–10 years (mean 4.7 years), treated in the Department of Otolaryngology, Head and Neck Surgery, in Homburg, Germany with APC (36 patients) or CO2 laser (28 patients) for tonsillar hyperplasia between June 2004 and December 2004 were available for analysis. Results: Forty-five (APC: 26 patients, CO2 : 19 patients) of the 64 patients (70.3%) could be contacted and were available for follow-up in a telephone survey conducted 10 years after surgery. The mean operation time was 17 min (range 10–25 min) in the APC group and 23 min (range 13–32 min) in the CO2 group (p = 0.0003). No case of intra- or postoperative bleeding was documented. One minor intraoperative complication in the form of a superficial lip burn was documented in the APC group. During the minimum 10 years of follow-up, 1 patient treated with APC underwent a surgical revision because of tonsillar regrowth, whereas in the group of patients treated with CO2, no surgical revision was needed. Regarding the parents' assessment of their children's symptoms, 89.4% of the parents of the CO2 laser group and 84.6% of the parents of the APC group reported that the overall long-term operation results of their children to be "very satisfying." Regarding complications, the need for secondary tonsillectomy, and parents' satisfaction, no statistically significant differences were found. Conclusions: Both CO2 laser tonsillotomy and APC tonsillotomy are safe procedures leading to very satisfying results with respect to intra- and postoperative complications.